Storage Characteristics of Staphylococcus xylosus-Fermented Low-Nitrite Sausages under Different Storage Durations and Packaging Methods - PANG Fan, SONG Enqiao, YANG Xiaoyin, MAO Yanwei, ZHANG Yimin, LIANG Rongrong, ZHU Lixian, DONG Pengcheng, NIU Lebao (Shipin Kexue, 2025)
In order to investigate the storage characteristics of Staphylococcus xylosus-fermented low-nitrite sausages under different storage durations and packaging methods, sausages were stored under vacuum skin packaging (VSP) or modified atmosphere packaging (MAP) and evaluated for sensory, physicochemical (color, pH, total volatile basic nitrogen (TVB-N) content, types and contents of volatile organic compounds) and microbial indicators (total viable count (TVC), number of Lactobacillus, Staphylococcus, Escherichia coli, Brochothrix thermosphacta, and microbial communities) after 0, 7, 14 and 21 days. The results showed that both packaging methods effectively maintained the low pH environment of fermented sausages. MAP significantly slowed down the increase in TVB-N content (P < 0.05) and inhibited microbial growth (P < 0.05), while VSP was more effective in preserving the good color of sausages, and resulted in significantly higher contents of volatile organic compounds and sensory scores compared with MAP (P < 0.05). In summary, VSP is more favorable for maintaining the color and flavor of fermented sausages, while MAP is more effective in extending the shelf life.